Efektivitas Penggunaan Aplikasi Telegram Guna Meningkatkan Hasil Belajar Siswa dalam Pembelajaran Daring Mata Pelajaran Perencanaan Bisnis - Suryandari, Chika Adinda; Saino, Saino (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research was conducted on 35 students and one of the teachers at SMK Negeri 1 Jombang in class X Online Business and Marketing 3 or X BDP 3. This study used a quantitative descriptive research method with the aim of knowing the effectiveness of using the telegram application as an online learning medium, to find out student learning outcomes when using the telegram application in online learning and to find out student responses to teachers when using the telegram application. Questionnaire, observation and documentation are data collection techniques in this study. This study used a hypothesis test T-test was used to determine the effectiveness of the effective telegram application as a learning medium on student learning outcomes. In the results of the study it was found that the use of the telegram application for teachers and students, for teachers, and for students was partially effective on learning outcomes. Keywords: Effectiveness, Telegram Application, Student Learning Outcomes